A new tectonic model for the contact relationships of Mesozoic and Cenozoic domains in the Principal Cordillera, Central Chile (33°-34° S) - Piñeiro, Tomas; Encinas, A.; Orts, D.; Henríquez, N.; Stinnesbeck, Wolfgang; Kietzmann, D.; Rossel, P.; Núñez, E.; Valencia, V. A. (Tectonics, 2025)
The origin of the contact between Cenozoic rocks of the Western Principal Cordillera (WPC) and Mesozoic rocks of the Eastern Principal Cordillera (EPC) in the Chilean Andes at 33°-34°S has been debated for several years. Most authors interpret this boundary as a regional-scale inverted fault that, during the early Miocene, thrust strata of the extensional Eocene-early Miocene Abanico Basin from the WPC over Mesozoic rocks of the EPC. To better constrain the nature of this boundary and determine the tectonostratigraphic evolution of this area of the Andes, we integrate new stratigraphic, structural, and geochronologic data. Our results indicate that faults previously interpreted as the boundary between the WPC and the EPC are, in fact, depositional contacts. The only fault we observed at the contact between these domains is the east-verging, generally overturned Las Arenas Fault that thrusts Mesozoic rocks over Cenozoic strata. Consequently, the boundary between the WPC and the EPC does not correspond to an inverted normal fault along the eastern margin of the Abanico Basin. Our structural analysis also suggests that Andean deformation initially propagated eastward during the early-middle Miocene and subsequently shifted westward in the middle-late Miocene, re-deforming both Mesozoic and Cenozoic rocks previously affected by east-verging structures. We also highlight previously undocumented synorogenic deposits younger than 13.6 Ma, along with new geochronologic constraints for the basal Abanico Formation (∼21-18 Ma), which are younger than reported in earlier studies.
Gesehen am 17.02.2026
Online veröffentlicht: 7. November 2025